Gelated microvesicle–mediated delivery of mesenchymal stem cell mitochondria for the treatment of myocardial infarction - Qi Chu; Dong He; Wenqi Xie; Shichun Li; Zixuan Dong; Xiaoling Fu (Proceedings of the National Academy of Sciences, 2025)
Mitochondrial dysfunction is closely linked to cardiomyocyte injury following myocardial infarction (MI). While mitochondrial transplantation is a promising therapeutic strategy, challenges remain in maintaining mitochondrial structural integrity, enhancing delivery efficiency, and increasing the mitochondrial supply. Herein, we developed a gelated microvesicle–based mitochondria delivery system (Mito@Microgels) for transplanting mesenchymal stem cell mitochondria, addressing the aforementioned issues. Further decoration of phosphatidylserine on the surface of Mito@Microgels boosted cellular uptake efficiency by cardiomyocytes. These Mito@Microgels effectively deliver active mitochondria to cardiomyocytes, improving the mitochondrial network architecture and function and consequently reducing the cellular injury induced by oxidative stress. Moreover, Mito@Microgels attenuated the inflammatory phenotype of macrophages, helping resolve excessive local inflammation. In vivo animal studies using a rat MI model further validated the therapeutic efficacy of the Mito@Microgels, as evidenced by improved myocardial function, prevention of infarcted left ventricular wall thinning, and increased cardiomyocyte survival. Our study introduces an efficient mitochondrial delivery strategy with significant potential for cardiac repair post-MI and other mitochondria-related diseases.